Konsep dan Implementasi Merdeka Belajar pada Evaluasi Pembelajaran Pendidikan Agama Islam - Salman Hudri; Khotibul Umam (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
This paper aims to determine the effect of the concept of merdeka belajar and its implications in the evaluation of Islamic Religious Education Learning. This paper uses a qualitative approach and literature study methods. Based on the results of the discussion, evaluation consists of measurement and assessment. In the context of learning, evaluation has a very important and strategic position, because it is included in the learning steps. The aim is to determine the effectiveness and efficiency of the learning system. The scope includes evaluation in learning programs, learning processes, and learning outcomes. In general, the evaluation principles consist of continuity, comprehensive, fair, objective, cooperative, and practical. Specifically, the principles consist of coherence, coherence, pedagogy, and accountability. Based on the literature review that has been carried out, the policy of the Ministry of Education and Culture, Nadiem Makarim, is known as the